On securitization, market completion and equilibrium risk transfer - Ulrich Horst; Traian A. Pirvu; Gonçalo Dos Reis (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2010)
We propose an equilibrium framework within which to price financial securities written on non- tradable underlyings such as temperature indices. We analyze a financial market with a finite set of agents whose preferences are described by a convex dynamic risk measure generated by the solution of a backward stochastic differential equation. The agents are exposed to financial and non-financial risk factors. They can hedge their financial risk in the stock market and trade a structured derivative whose payoff depends on both financial and external risk factors. We prove an existence and uniqueness of equilibrium result for derivative prices and characterize the equilibrium market price of risk in terms of a solution to a non-linear BSDE.
Keywords: G12; D52; C62; C68; 330; Backward stochastic differential equations; dynamic risk measures; partial equilibrium; equilibrium pricing; market completion; Securitization; Portfolio-Management; Unvollkommener Markt; Optionspreistheorie; Gleichgewicht; Theorie